URGENSI PEMBENTUKAN INDONESIA SEA AND COAST GUARD SEBAGAI PELAKSANAAN KONVENSI INTERNATIONAL MARITIME ORGANIZATION (IMO) MENGENAI KEAMANAAN LAUT - Liberta Bintoro Ranggi Wirasakti; Siti Muslimah (Faculty of Law Universitas Sebelas Maret, 2015)
This study aims to determine the legal significance of the establishment of Indonesian Sea and Coast Guard, analyze threats in Indonesian waters, overlapping law enforcement and maritime security in Indonesia and conventions issued by the International Maritime Organization relating to marine safety. This research is a normative legal research that is prescriptive. Types and sources of materials used in this research is the primary legal materials and secondary legal materials. The data collection techniques by means of literature. While the analysis uses legal interpretation. Based on the conclusions generated discussion needs to establish Indonesian Sea and Coast Guard to conduct maritime security and implement IMO conventions concerning maritime safety and the safety of shipping.The establishment of Indonesian Sea and Coast Guard can be effective tools for implementation of IMO convention relating to marine safety.